2015
DOI: 10.3390/polym7040610
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Simulation of Hyperbranched Polymers

Abstract: In a previous work, we described a multi-scale protocol for the simulation of the conformation and dynamics of macromolecules that was applied to dendrimer molecules proving its predictive capability by comparison with experimental data. That scheme is now employed in order to predict conformational properties (radius of gyration) and overall hydrodynamic properties (translational diffusion and intrinsic viscosity) of hyperbranched molecules in dilute solution. For that purpose, we use a very simple coarse-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Without imposing the attachment probability parameter (meaning equal probability with p = 0), hyperbranched polymers built with the SG model have DB = 0.6 to 0.8, whereas polymers built with QG lead to DB ∼ 0.5, indicating these methods induce different classes of hyperbranched structures. We observed that the DB value changes if the probability changes, and the DB converges to a specific value as the number of monomers N increases (Figure S2), similar to the formula suggested by Schmidt and co-workers . However, the behavior of the DB values does not agree with the formula for small N values.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Without imposing the attachment probability parameter (meaning equal probability with p = 0), hyperbranched polymers built with the SG model have DB = 0.6 to 0.8, whereas polymers built with QG lead to DB ∼ 0.5, indicating these methods induce different classes of hyperbranched structures. We observed that the DB value changes if the probability changes, and the DB converges to a specific value as the number of monomers N increases (Figure S2), similar to the formula suggested by Schmidt and co-workers . However, the behavior of the DB values does not agree with the formula for small N values.…”
Section: Resultssupporting
confidence: 76%
“…Here T , L , and D specify the number of terminal, linear, and dendritic units, respectively . In order to obtain structures with the target degree of branching (0.5), we applied an additional constraint to the attachment probability parameter p = 0.2, which indicates the ratio of the probability of introducing a new node to linear nodes (i.e., secondary amine) to terminal nodes (i.e., primary amine). In both cases we prohibit formation of cyclic rings.…”
Section: Model and Simulations Methodsmentioning
confidence: 99%
“…For example, at [DM]/[M] = 0.02, α = 0.55, indicative of flexible chains similar in character to perfectly linear PMMA. The impact of branch length on the scaling behavior was recently demonstrated by Schmidt et al by multiscale simulation . In their work, four monomers with varied Kuhn lengths are used to calculate polymer properties as a function of molecular weight using atomistic Langevin calculations with a coarse-grained bead-and-spring model.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of branch length on the scaling behavior was recently demonstrated by Schmidt et al by multiscale simulation. 42 In their work, four monomers with varied Kuhn lengths are used to calculate polymer properties as a function of molecular weight using atomistic Langevin calculations with a coarsegrained bead-and-spring model. They predict that polymers with shorter branches have a smaller α value (more globular) in agreement with our findings.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, HBPs under shear flow 44 45 and elongational flow 46 , the conformational behavior of charged/uncharged HBPs in solution 47 and the influence of the Wiener index 48 on the intrinsic viscosity and radius of gyration 49 were investigated by Adolf and Karatasos et al Nevertheless, these models are still deviated from the actual polydisperse HBPs. The third type of models has sincerely considered the polydispersity of HBPs, and was developed by Ricardo Rodríguez Schmidt and coworkers 50 51 . In this model, they firstly obtained the coarse-grained model parameters from atomic-level simulations of small chains fragments, and then they used the Monte Carlo technique to generate a set of polydisperse HBPs with required DBs .…”
mentioning
confidence: 99%